Effect of health capital on the economic growth process of Iranian provinces using generalized method of moments approach - Mojtaba Ghiasi; Ahmad Sarlak; Hadi Ghafari (Gonabad University of Medical Sciences, 2019)
Many studies have been conducted on the relationship between education as an indicator of human capital and economic growth in our country. However, there have been a few studies regarding the simultaneous impact of health capital and education indicators on the economic growth of the provinces up to now. In this regard, the present study examined the impact of human health indicators and educational expenditures on the economic growth of the provinces of Iran. In this study, the dynamic effect of health capital indicators and educational expenditure along with the performance of the capital assets ownership on the growth of the economies was examined using the panel data obtained from the provinces during the years 2005-2015 by employing the generalized method of moments. The study results indicate that the fertility rate with a coefficient of 0.39, life expectancy with a coefficient of 0.202, and growth of household health expenditures with a coefficient of 0.045 had a positive effect on the economic growth of the provinces. However, the mortality rate with a coefficient of 0.203 had a significant negative effect on the provinces economic growth during the years under study. It was also found that educational expenditures growth and performance of capital assets ownership had a significant positive effect on the economic growth of the provinces. The health capital and its indicators are a long-term investment that should be considered as an important priority by the policymakers of the country and provinces.